PEMBELAJARAN LUAS DAERAH BANGUN DATAR DI SEKOLAH DASAR - Yuza, Arlina (Menara Ilmu, 2018)
One characteristic of good mathematics learning is the presentation of learning based onthe theory of learning psychology. This means that the teacher must design a lesson thatsuits the stages of a student's mental development. The stage of mental development ofelementary school students is at the concrete operational stage because their age is in therange of age 7 to 11 years. Therefore, mathematics learning in elementary school shouldbe able to facilitate students to acquire concepts. Learning to wake up flat becomes a veryimportant thing to note because this material becomes a prerequisite on the matter ofwaking up space. The concept of two-dimentional figureshould be taught in a guidedmanner to the students, not just memorizing the formula alone.Key Words: two-dimentional figure, mathematics, elementaray school